2017
DOI: 10.1038/srep40292
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Structure and Enzymatic Activity Profile of a Core Papain-like Protease of MERS Coronavirus with utility for structure-based drug design

Abstract: Ubiquitin-like domain 2 (Ubl2) is immediately adjacent to the N-terminus of the papain-like protease (PLpro) domain in coronavirus polyproteins, and it may play a critical role in protease regulation and stability as well as in viral infection. However, our recent cellular studies reveal that removing the Ubl2 domain from MERS PLpro has no effect on its ability to process the viral polyprotein or act as an interferon antagonist, which involves deubiquitinating and deISGylating cellular proteins. Here, we test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 32 publications
(82 reference statements)
2
49
1
Order By: Relevance
“…In contrast to the variable relative orientations of the Ubl domains and the catalytic domain of USP7, the Ubl2 domain is anchored to the CoV PL2 pro by two salt-bridges in MERS-CoV and SARS-CoV (Lei et al, 2014), so it is unlikely to regulate the catalytic activity of PL2 pro . In agreement with this conclusion, the presence or absence of the Ubl2 of SARS-CoV or MERS-CoV shows almost no effect on the PL2 pro activities (Frieman et al, 2009;Clasman et al, 2017).…”
Section: Ubiqutin-like Domain 2 (Ubl2)supporting
confidence: 78%
See 3 more Smart Citations
“…In contrast to the variable relative orientations of the Ubl domains and the catalytic domain of USP7, the Ubl2 domain is anchored to the CoV PL2 pro by two salt-bridges in MERS-CoV and SARS-CoV (Lei et al, 2014), so it is unlikely to regulate the catalytic activity of PL2 pro . In agreement with this conclusion, the presence or absence of the Ubl2 of SARS-CoV or MERS-CoV shows almost no effect on the PL2 pro activities (Frieman et al, 2009;Clasman et al, 2017).…”
Section: Ubiqutin-like Domain 2 (Ubl2)supporting
confidence: 78%
“…The PL2 pro adopts an extended right-hand fold with thumb, palm, and fingers subdomains, similar to the TGEV PL1 pro (Fig. 6; Ratia et al, 2006;Lei et al, 2014;Lee et al, 2015;Kong et al, 2015;Chen et al, 2015;Clasman et al, 2017; see also Table 1) and human USPs (e.g. USP14, USP7; Ratia et al, 2006).…”
Section: Papain-like Protease 2 (Pl2 Pro )mentioning
confidence: 74%
See 2 more Smart Citations
“…S1) and homology modeling, PEDV PL2 pro may be composed of four domains: ubiquitin-like (Ubl), palm, thumb and fingers domains. The latter three domains form a catalytic core and may retain catalytic activity, like that of SARS-and MERS-CoV PL pro s (Chou et al, 2012;Clasman et al, 2017;Lei et al, 2014). In the present study, we made a recombinant catalytic core PEDV PL2 pro and demonstrated its secondary, tertiary and quaternary structural characteristics.…”
Section: Introductionmentioning
confidence: 72%